0824 Sleep Habit Among Preschoolers: Comparison Between Children Attending Kindergartens and Nursery Schools. (27th April 2018) - Oka, Y; Itoh, K; Takata, N
Abstract: Introduction: Sleep habit in childhood is affected by daytime activity and school schedule. In most of the nursery schools in Japan, children take regular nap after lunchtime, but children usually do not take nap at kindergartens. The aim of the study was to elucidate the difference of sleep habits between children attending kindergartens and nursery schools. Methods: Child and Adolescent Sleep Questionnaire was distributed to children at the age of 4–5 attending kindergartens or nursery schools in Yamaguchi City, Japan. One hundred sixty nine responses were included in the analysis. Sleep habits including bedtime, wake time, sleep duration and sleep problems were compared between children attending kindergartens and nursery schools. Results: Mean duration of nap was 37.2 minutes/day among children attending nursery schools, which was significantly longer than children attending kindergartens (15.1 minutes/day). Mean time returning home was significantly later in children attending nursery schools (5:41pm) than in kindergarteners (3:01pm). Bedtime on weekdays and weekends were significantly later, and wake time on weekdays was significantly earlier in children attending nursery schools. Children attending nursery schools had more problem in falling asleep and bedtime resistance than kindergarteners. Conclusion: Children attending nursery schools take longer nap and returning home later, and they go to bed later and had more problems in initiating sleep. Regular nap at nursery schools was associated with sleep problems of preschoolers and may require some modification of the school schedule. Support (If Any): This research was supported by Health Labor Sciences Research Grant, Japan.